Effects of Age-Related Macular Degeneration on Postural Sway - Chatard, Hortense; Tepenier, Laure; Jankowski, Olivier; Aussems, Antoine; Allieta, Alain; Beydoun, Talal; Salah, Sawsen; Bucci, Maria P. (Frontiers in Human Neuroscience, 2017)
PURPOSE: To compare the impact of unilateral versus bilateral age-related macular degeneration (AMD) on postural sway, and the influence of different visual conditions. The hypothesis of our study was that the impact of AMD will be different between unilateral and bilateral AMD subjects compared to age-matched healthy elderly. METHODS: Postural stability was measured with a platform (TechnoConcept®) in 10 elderly unilateral AMD subjects (mean age: 71.1 ± 4.6 years), 10 elderly bilateral AMD subjects (mean age: 70.8 ± 6.1 years) and 10 healthy age-matched control subjects (mean age: 69.8 ± 6.3 years). Four visual conditions were tested: both eyes viewing condition (BEV), dominant eye viewing (DEV), non-dominant eye viewing (NDEV) and eyes closed (EC). We analyzed the surface area, the length, the mean speed, the anteroposterior (AP) and mediolateral (ML) displacement of the center of pressure (CoP). RESULTS: Bilateral AMD subjects had a surface area (p<0.05) and AP displacement of the CoP (p<0.01) higher than healthy elderly. Unilateral AMD subjects had more AP displacement of the CoP (p<0.05) than healthy elderly. CONCLUSIONS: We suggest that ADM subjects could have poor postural adaptive mechanisms leading to increase their postural instability. Further studies will aim to improve knowledge on such issue and to develop reeducation techniques in these patients.